Process and Storage Stability of Bacillus coagulans LBSC in Food Matrices and Appraisal of Calorific Restriction: B. coagulans LBSC stability and calorie restriction - Maity, Chiranjit; Bagkar, Pratik; Dixit, Yogini; Tiwari, Amit; Gupta, Anil Kumar (Applied Food Biotechnology, 2020)
Background and Objective: Probiotic bacteria as food additives have led to a significant growth in functional food levels. Functional foods present multiple challenges to probiotic viability and stability. In the present study, Bacillus coagulans LBSC DSM 17654, a probiotic strain, was incorporated into various foods to assess its stability during processing and storage and ability to decrease food calorie contents. Material and Methods: Bacillus coagulans LBSC was used to prepare various beverages and foods such as hot and cold non-alcoholic beverages, breakfast cereals, oral rehydration salts, confections, frostings, convenience foods, frozen dairy desserts, condiments, relishes, fermented milk beverages and cough syrups. The bacterial process and storage stabilities were assessed using relative viability estimation. Stability of Bacillus coagulans LBSC was assessed in aqueous suspensions following ICH guidelines [Q1A (R2)] under various temperatures (0-100 ºC). Strain was assessed for its in vitro calorie restriction capabilities when incorporated into foods. Results and Conclusion: Bacillus coagulans LBSC survived well during food processing (relative viability of 99.46% ±0.49) and storage (relative viability of 99.22% ±0.51) conditions. The bacterium was stable in aqueous suspension and tolerated high temperatures well (relative viabilities of 99.56% ±0.21 and 97.59% ±0.01 at 80 and 90 ºC, respectively). Bacillus coagulans LBSC showed significant in vitro calorie decreases in probiotic supplemented foods, compared to foods with no supplementations (p < 0.05). In conclusion, Bacillus coagulans LBSC exhibited good stability in aqueous media at high temperatures. Bacillus coagulans LBSC was not only stable in a wide spectrum of food categories, it could grow on foods to decrease food calorie under in vitro conditions; suggesting its uses as a functional food ingredient for better management of obesity and ageing and their associated health risks. Conflict of interest: The authors declare no conflict of interest.